2023
DOI: 10.1002/osi2.1206
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of oral health and its impact on the quality of life of patients with Sjögren's syndrome

Abstract: ObjectivesThis study aimed to describe the clinical profile and the oral health status and their impact on the quality of life of patients with Sjögren's syndrome (SS).MethodsThrough a cross‐sectional study, patients with SS were compared with those with dry symptoms with no conclusive diagnosis of SS (non‐SS) and patients without complaints of dryness, matched for sex and age (control group). Data related to classification of SS, focus score, unstimulated whole salivary flow (UWSF), dental plaque index, perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The study by Tashbayev et al [ 36 ] demonstrated low risk across all domains, suggesting a generally robust study design and conduct. Similarly, the study by Galves et al [ 37 ] exhibited consistently low risk across all domains, indicating a high level of methodological quality. Overall, one study [ 35 ] showed a moderate risk of bias, while two studies [ 36 , 37 ] were deemed at low risk of bias ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 65%
See 4 more Smart Citations
“…The study by Tashbayev et al [ 36 ] demonstrated low risk across all domains, suggesting a generally robust study design and conduct. Similarly, the study by Galves et al [ 37 ] exhibited consistently low risk across all domains, indicating a high level of methodological quality. Overall, one study [ 35 ] showed a moderate risk of bias, while two studies [ 36 , 37 ] were deemed at low risk of bias ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 65%
“…Similarly, the study by Galves et al [ 37 ] exhibited consistently low risk across all domains, indicating a high level of methodological quality. Overall, one study [ 35 ] showed a moderate risk of bias, while two studies [ 36 , 37 ] were deemed at low risk of bias ( Figure 5 ). None of the studies was judged at high risk of bias.…”
Section: Resultsmentioning
confidence: 65%
See 3 more Smart Citations